Moesin-dependent cytoskeleton remodelling is associated with an anaplastic phenotype of pancreatic cancer - Abiatari, Ivane; Esposito, Irene; Oliveira, Tiago De; Felix, Klaus M.; Xin, Hong; Penzel, Roland; Giese, Thomas; Friess, Helmut; Kleeff, Jörg (Journal of cellular and molecular medicine, 2010)
Cell motility is controlled by the dynamic cytoskeleton and its related proteins, such as members of the ezrin/radixin/moesin (ERM) family, which act as signalling molecules inducing cytoskeleton remodelling. Although ERM proteins have been identified as important factors in various malignancies, functional redundancy between these proteins has hindered the dissection of their individual contribution. The aim of the present study was to analyse the functional role of moesin in pancreatic malignancies. Cancer cells of different malignant lesions of human and transgenic mice pancreata were evaluated by immunohistochemistry. For functional analysis, cell growth, adhesion and invasion assays were carried out after transient and stable knock-down of moesin expression in pancreatic cancer cells. In vivo tumourigenicity was determined using orthotopic and metastatic mouse tumour models. We now show that moesin knock-down increases migration, invasion and metastasis and influences extracellular matrix organization of pancreatic cancer. Moesin-regulated migratory activities of pancreatic cancer cells were in part promoted through cellular translocation of β-catenin, and re-distribution and organization of the cytoskeleton. Analysis of human and different transgenic mouse pancreatic cancers demonstrated that moesin is a phenotypic marker for anaplastic carcinoma, suggesting that this ERM protein plays a specific role in pancreatic carcinogenesis.